Tibial plateau leveling osteotomy for the treatment of cranial cruciate ligament rupture in a dog: case report - Honda, Claudia Natsuki (2024)
The complete or partial rupture of the cranial cruciate ligament (CCRL) results in the loss of stabilization of the knee joint, which is one of the main causes of claudication of the pelvic limb, mainly due to the intense pain caused. Still, the rupture of the cranial cruciate ligament is a condition of considerable casuistry in dogs whose cause is considered multifactorial, without sexual predisposition with greater and prevalence in large and obese dogs. In addition to the clinical disorder, CCL tear can lead to complications that include inflammation of the synovial membrane, osteoarthritis, meniscus injury, and degenerative joint disease. The diagnosis is made through the cranial drawer test and tibial compression, in addition to radiographic confirmation. One of the surgical techniques for correction of CCL tear is the tibial plateau leveling osteotomy (TPLO), which has the morphofunctional objective of altering the anatomical angulation through osteotomy, rotation and stabilization of the proximal portion of the tibia. The change in biomechanics restricts joint activation, causing dynamic neutralization of the cranial tibial stimulus. In view of the data, the work aims to present a TPLO performed in a 9-year-old dog, mixed breed, with an effective result without postoperative complications.